From Religious Spirit to Social Innovation: Transforming Agricultural Tourism in Alamendah Based on Pesantren - Daniswara, Nirwasita; Sutinah (Ri'ayah: Jurnal Sosial dan Keagamaan, 2024)
This study discusses the agricultural transformation in Alamendah Village, Bandung Regency, spearheaded by Pesantren Al-Ittifaq. Through the integration of religious values, social innovation, and agricultural education, this pesantren has successfully driven community-based social and economic change. This research uses a qualitative approach with a case study method to explore how local leadership, especially through the figure of Kiai Fuad, is able to change the mindset of the community from traditional agriculture to more modern strawberry cultivation. This transformation not only lifted local economic welfare, but also strengthened social solidarity through cooperative development and active community participation in collective decision-making. This research underscores the importance of social and symbolic capital in creating sustainable development based on local potential. The conclusion of this article suggests that the community-based development model implemented in Alamendah is capable of becoming an example of replication for other regions that seek to create holistic and inclusive welfare while maintaining cultural and religious values.